Improving the Effectivity of Urea Fertilizer in Shallot by Using Urease and Nitrification Inhibitors - Sugiyanta Sugiyanta; Isna Tustiyani; Diny Dinarti (Institut Pertanian Bogor, 2019)
Nitrification inhibitors are used to decrease the rate of nitrification process so it can decreases the nitrate losses. The objective of this study was to investigate the improvement of urea effectiveness by using urease and nitrification inhibitors on shallot. The study was conducted at Blubuk Village, Tanjung, Brebes District, Central Java, Indonesia from December 2017 to April 2018. The experiment was arranged in a randomized block design with 8 treatments and 3 replications. The treatments were untreated group (P0), 100% dose of Urea without inhibitor (control) (P1), (3) 100% dose of Urea + Urease Inhibitor (P2), 100% dose of Urea + Nitrification Inhibitor (P3), 100% dose of Urea + Urease Inhibitor + Nitrification Inhibitor (P4), 80% dose of Urea + Urease Inhibitor (P5), 80% dose of Urea + Nitrification Inhibitor (P6), and 80% dose of Urea + Urease Inhibitor + Nitrification Inhibitor (P7). The results showed that 100% dose of Urea + Urease inhibitor, 80% dose of Urea + Urease inhibitor, 80% dose of Urea + Nitrification inhibitor, and 80% dose of Urea + Urease inhibitor + Nitrification inhibitor treatments significantly produced higher plants heights, number of leaves, and more number of tillers compared to control treatment (100% Urea without inhibitors), without affecting the yield and yield components.